290 Targeting AKT and DNA-PK as a therapeutic strategy in platinum resistant high-grade serous ovarian cancer. (4th December 2020) - Rinne, Natasha; Yuan, Shengnan; Fotopoulou, Christina; Gabra, Hani; Cunnea, Paula
Abstract : Introduction/Background: High-grade serous ovarian cancer (HGSOC) is the most lethal form of gynaecological malignancy. Despite initial sensitivity to platinum chemotherapy, the majority of patients develop resistance to treatment and eventually die. Current treatment options for platinum-resistant patients are limited. The role of the PI3K/AKT/mTOR pathway has been described in chemo-resistant HGSOC, in particular through activation of AKT by DNA-PK in response to platinum treatment. As increasing numbers of AKT and DNA-PK inhibitors advance to clinical trials, determining mechanism of action and efficacy is crucial. This project aims to evaluate inhibition of AKT or DNA-PK as a therapeutic strategy to target platinum resistance in HGSOC, and identify proteomic signatures confirming mechanism of action and target inhibition. Methodology: A panel of seven AKT and DNA-PK inhibitors were tested in combination with cisplatin chemotherapy in immortalised HGSOC cell lines and primary tumour cells cultured from HGSOC tumour/ascites samples. Clonogenic assays were performed to establish effect of inhibitor treatment in combination with cisplatin chemotherapy on the ability of cells to form colonies. Isobologram assays were performed to establish synergy/antagonism between inhibitors and cisplatin chemotherapy. Proteomic Reverse Phase Protein Array (RPPA) was performed to determine the mechanism of action of inhibitors, and results were confirmed with immunoblotting. Results: Treatment with AKT or DNA-PK inhibitors in combination with cisplatin led to significantly enhanced apoptotic responses in immortalised platinum-resistant HGSOC cell lines (n=5), and in primary cells derived from ascites or tumour (n=4, p<0.01, p<0.05), compared to cisplatin treatment alone. In platinum-resistant HGSOC cell lines, fewer cell colonies were observed with increasing concentrations of AKT or DNA-PK inhibitors in combination with cisplatin (n=3) in comparison with cisplatin alone. Varying synergistic effects were observed across the panel of inhibitors when combined with cisplatin; Uprosertib (AKT inhibitor) in particular displayed strong synergy with cisplatin (Loewe analysis). Proteomic analysis of inhibitor treatment in HGSOC platinum-resistant cells demonstrated the mechanism of action of Uprosertib in targeting the PI3K/AKT pathway. Conclusion: In platinum-resistant HGSOC cells, AKT or DNA-PK inhibition functioned synergistically with cisplatin and reduced cell growth and proliferation. In both immortalised and primary HGSOC cell lines tested, AKT or DNA-PK inhibition significantly enhanced the apoptotic response to cisplatin demonstrating the efficacy of AKT or DNA-PK as potential therapeutic targets in chemoresistant HGSOC. By improving patient response to treatment, AKT and DNA-PK inhibitors could expand the therapeutic options for patients with platinum-resistant HGSOC, improving overall survival. Disclosures: CF: advisory boards and honoraria from Roche, Tesaro, Sequana, Olympus, Astra Zeneca. Other authors have no conflict of interest.